KNOWLEDGE AND ATTITUDE OF PALLIATIVE CARE AMONG UNDERGRADUATE NURSING STUDENTS IN MALAYSIA - Emi Hussien; Wulan Noviani; Wan Aisyah W. Ibrahim; Che Azunie Che Abdullah; Suzilawati Mohamed Ariffin (Journal of Islamic, Social, Economics and Development, 2024)
Palliative care comprises a collection of care that nurses should provide to patients in need, aiming to enhance their quality of life, particularly among those facing life-threatening illnesses. Among these barriers are a lack of awareness regarding palliative care, insufficient training in palliative care provision, misconceptions about the concept of palliative care, and healthcare policies and delivery systems that do not incorporate palliative care. Consequently, this situation underscores the significance of this study, which aims to assess the current knowledge and attitudes towards palliative care among nursing students. Nurses play a crucial role in delivering care to individuals and their families, thereby ensuring optimal treatment in the future. This study aims to determine the level of knowledge and attitudes towards palliative care among nursing students. A quantitative cross-sectional study employing convenience sampling was conducted among 180 nursing students (Year 2–4) at a public university in Malaysia from April to June 2023. Data were collected through Google Forms surveys, distributed to respondents in English. Data analysis was performed using SPSS version 26, employing independent T-tests and Spearman correlation. Most undergraduate nursing students demonstrated poor understanding and harboured negative attitudes towards palliative care. Additionally, a positive correlation was observed between the level of knowledge and attitudes among the students. It is imperative to strengthen palliative care education into the nursing curriculum to foster a deeper understanding of the concept among students.